Abamectin affects the bioenergetics of liver mitochondria: A potential mechanism of hepatotoxicity - Castanha Zanoli, Juliana C. [UNESP] (2012)
Abamectin (ABA) is a macrocyclic lactone of the avermectin family used worldwide as an antiparasitic agent in farm animals and pets and as the active ingredient of insecticides and nematicides. In this study, the effects of abamectin on the bioenergetics of mitochondria isolated from rat liver were evaluated. Mitochondria are responsible for converting the energy released by electron transport and stored as the binding energy molecule ATP. Xenobiotics that interfere with its synthesis or utilization can be acutely or chronically toxic. Abamectin (5-251 mu M) caused concentration-dependent inhibition of the respiratory chain without affecting the membrane potential or the activity of enzymes NADH dehydrogenase or succinate dehydrogenase. This behavior is similar to oligomycin and carboxyatractyloside and suggests direct action on F0F1-ATPase and/or the adenine nucleotide translocator (ANT). ABA more pronouncedly inhibited ATPase phosphohydrolase activity in intact, uncoupled mitochondria than in freeze-thawed disrupted mitochondria. ADP-stimulated depolarization of the mitochondrial membrane potential was also inhibited by ABA. Our results indicate that ABA interacts more specifically with the ANT, resulting in functional inhibition of the translocator with consequent impairment of mitochondria! bioenergetics. This effect could be involved in the ABA toxicity to hepatocytes. (C) 2011 Elsevier Ltd. All rights reserved.